Rechargeable hybrid aqueous batteries using silica nanoparticle doped aqueous electrolytes. (15th May 2016) - Lu, Changyu; Hoang, Tuan K.A.; Doan, The Nam Long; Zhao, Hongbin; Pan, Ran; Yang, Li; Guan, Weisheng; Chen, P.
Highlights: The first use of silica nanoparticle doped electrolyte has been demonstrated. Enhancement of open-circuit voltage is observed when batteries are under storage. Decrease in back-current is observed when batteries are under constant charging. Enhancement of rate capability and cycle life are observed. Abstract: Silica nanoparticles doped aqueous electrolytes have been prepared and implemented for the first time in rechargeable hybrid aqueous battery systems (ReHABs). The batteries were assembled from a cathode containing LiMn2 O4 – a lithium intercalation compound, a zinc metal foil anode and a sulfate electrolyte containing Zn 2+ and Li + ions. Silica nanoparticles were doped into the liquid electrolyte with the initial aim to create a silica containing gel electrolyte. However, the 5% and 10% SiO2 doped electrolytes were viscous and could be easily absorbed in the Absorbed Glass Mat (AGM) separator and the whole system (doped electrolyte + AGM) immobilized after a few minutes. The AGM loaded with silica doped electrolytes remained wet after storage for weeks under ambient condition thanks to the water retention ability of nanoscale silica particles. The doped silica nanoparticles restrained deposition of zinc dendritic crystals, and reduced float charge current and self-discharge. The ReHABs assembled from the silica nanoparticles doped electrolytes provided high specific discharge capacity, up to 140 mAh (g LiMn2 O4 ) − 1 at 0.2 C, and the cyclability of such systems was significantly enhanced compared to the ReHABs assembled from conventional electrolytes. X-ray Diffraction revealed that the anode of the batteries using SiO2 doped electrolytes were protected since only the XRD peaks of Zn were detected after the batteries were running 700 cycles of charge and discharge.